Method of detection of http attacks on a smart home using the algebraic matching method - Gorbatiuk, V.O.; Gorbatiuk, S.O. (Проблеми програмування, 2022)
All international and domestic spheres of production and service are developing at a frantic pace, and in modern life it is no longer possible to imagine any enterprise or government institution without connecting to the Internet and using cloud services. The development of digital technologies forces the application of innovative solutions in everyday life and entertainment. In our modern age with society’s current dependence on high-tech gadgets and the Internet, we can definitely mark the emergence of smart home technology. In this regard, interest in private information on the network is growing, more approaches to attacks are appearing, cybercrime is becoming more organized, and its level is increasing. This work aims to show the types of cyber attacks on smart homes, as well as tools and methods for their detection, in particular, the method of mathematical comparison, which provides an opportunity to create stable web applications and services, taking into account the requirements for their security and reliability.